Prosa : Geschichte, Poetik, Theorie - Bezantakou, Olga; Brokoff, Jürgen; Del Valle Lattanzio, Camilo; Dimitriadis, Pavlos; Efimova, Svetlana; Efimova, Svetlana; Emundts, Dina; Ette, Wolfram; Fuchs, Florian; Gamper, Michael; Gamper, Michael; Hansen-Löve, Aage A.; et al. (WeltLiteraturen / World Literatures, 2021)
"Prose" refers to a largely free mode of speaking and writing that is not tethered to any normative form, and which permits a wide range of composition styles due to the openness of its content and form. In 18 chapters, this volume makes "prose"--An important but thus far insufficiently examined category of literary studies - the subject of historical, methodological, and theoretical investigations